Relationship of Serum Ferritin Levels with Haemoglobin Percentage and Its Impact on Fetomaternal Outcome of the Pregnancy: Serum Ferritin Levels with Haemoglobin Percentage and Its Impact on Fetal-Maternal Outcome - Salman, Nayla; Awan, Azra Saeed; Fatima, Touseef; Maqsood, Umaira; Kousar, Shermeen; Ahmed, Madiha; Jamil, Bushra (Pakistan Journal of Health Sciences, 2026)
Iron stores in the body exist primarily in the form of ferritin. Low serum ferritin levels, even in females with ideal haemoglobin levels, can lead to poor fetal-maternal outcome. Objective: To determine the frequency of low serum ferritin in non-anaemic pregnant females and its Fetomaternal outcomes. Methods: This Comparative analytical study was carried out in the Department of Gynaecology and Obstetrics, Fauji Foundation Hospital, Rawalpindi. Patients were enrolled from the Fauji Foundation Hospital, Rawalpindi. Detailed history was taken, and pregnant females with normal haemoglobin were selected; their serum ferritin was followed. Patients with low serum ferritin levels were observed for maternal and fetal outcomes. Data were entered and analysed by SPSS version 25.0. RESULTS: The mean age of cases was 29.95 ± 3.57 years, with minimum and maximum ages of 25 and 35 years. Low serum ferritin levels were found in 248 (46.44%) cases, while in 286 (53.56%) cases serum ferritin levels were normal. 16 (21.72%) neonates were born preterm, 285 (53.37%) females had C-section, 41 (7.68%) had PPH, 96 (17.98%) neonates had low birth weight, and 94 (17.60%) neonates needed an ICU admission. Significant association of this outcome with low serum levels was found, p-value<0.001. Conclusions: The females with Hb levels ≥ 11g/dl should be screened for their serum ferritin levels, as females with low serum ferritin levels were associated with poor maternal outcome, like C-section, NICU admission, PPH, and poor fetal outcome, like preterm birth and low birth weight.